2016
DOI: 10.1021/acs.jmedchem.6b01178
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Additive Approach for Alzheimer’s Disease Therapy: New Ferulic (Lipoic) Acid Plus Melatonin Modified Tacrines as Cholinesterases Inhibitors, Direct Antioxidants, and Nuclear Factor (Erythroid-Derived 2)-Like 2 Activators

Abstract: Novel multifunctional tacrines for Alzheimer's disease were obtained by Ugi-reaction between ferulic (or lipoic acid), a melatonin-like isocyanide, formaldehyde, and tacrine derivatives, according to the antioxidant additive approach in order to modulate the oxidative stress as therapeutic strategy. Compound 5c has been identified as a promising permeable agent showing excellent antioxidant properties, strong cholinesterase inhibitory activity, less hepatotoxicity than tacrine, and the best neuroprotective cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 40 publications
1
69
0
Order By: Relevance
“…Despite extensive evidence of high levels of oxidative stress in AD brains, Nrf2 is predominantly cytoplasmic in neurons, demonstrating the failure of this pathway20. Thus, the Nrf2-EpRE pathway has emerged as a promising pharmacological target for the treatment of AD212223242526. Furthermore, there is evidence that the activities of GSK3β and Nrf2 are negatively correlated, thus increasing neuronal sensitivity to oxidative stress in AD2728.…”
mentioning
confidence: 99%
“…Despite extensive evidence of high levels of oxidative stress in AD brains, Nrf2 is predominantly cytoplasmic in neurons, demonstrating the failure of this pathway20. Thus, the Nrf2-EpRE pathway has emerged as a promising pharmacological target for the treatment of AD212223242526. Furthermore, there is evidence that the activities of GSK3β and Nrf2 are negatively correlated, thus increasing neuronal sensitivity to oxidative stress in AD2728.…”
mentioning
confidence: 99%
“…Previous studies concentrated on the effect of LA on diabetes, obesity, and Alzheimer disease [12,13,15,23]. LA supplementation was found to be a potential treatment for the observed loss of cellular energetics in Alzheimer disease and it could potentiate the antioxidant defense system to prevent or delay the oxidative stress in the progression of this devastating dementing disorder [15,23]. However, few studies were focused on the effect of LA on age-related cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…As the strongest anti-oxidant small molecule chemical to date, LA is widely used in the treatment and prevention of various diseases [12,13,14]. Some animal studies have shown that LA may have effect on Alzheimer disease [15]. However, at present, there is no reports about whether LA treatment can prevent or delay the decline of learning and memory caused by aging.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several MTDLs have been developed by many research groups [ 5 , 6 , 7 , 8 ]. In the last decade, we have contributed to this area by using multicomponent reactions (MCR) [ 9 , 10 , 11 , 12 , 13 ] as a very suitable and efficient synthetic tool, with its easy performance and its time-saving procedure leading a higher structural diversity.…”
Section: Introductionmentioning
confidence: 99%